Considerations for the Bioengineering of Advanced Cardiac In Vitro Models of Myocardial Infarction. Issue 15 (19th January 2021) - Sharma, Poonam; Wang, Xiaowei; Ming, Clara Liu Chung; Vettori, Laura; Figtree, Gemma; Boyle, Andrew; Gentile, Carmine
Abstract: Despite the latest advances in cardiovascular biology and medicine, myocardial infarction (MI) remains one of the major causes of deaths worldwide. While reperfusion of the myocardium is critical to limit the ischemic damage typical of a MI event, it causes detrimental morphological and functional changes known as "reperfusion injury." This complex scenario is poorly represented in currently available models of ischemia/reperfusion injury, leading to a poor translation of findings from the bench to the bedside. However, more recent bioengineered in vitro models of the human heart represent more clinically relevant tools to prevent and treat MI in patients. These include 3D cultures of cardiac cells, the use of patient‐derived stem cells, and 3D bioprinting technology. This review aims at highlighting the major features typical of a heart attack while comparing current in vitro, ex vivo, and in vivo models. This information has the potential to further guide in developing novel advanced in vitro cardiac models of ischemia/reperfusion injury. It may pave the way for the generation of advanced pathophysiological cardiac models with the potential to develop personalized therapies. Abstract : Major molecular, cellular, and extracellular features typical of a heart attack in humans together with a direct comparison of currently available in vivo, ex vivo, and in vitro models are summarized in this review article with the goal to generate advanced bioengineered in vitro models better recapitulating the complex in vivo microenvironment typical of an infarcted heart.